2021
DOI: 10.3389/fcell.2021.702112
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Metabolic and Immune Landscape of Non-small Cell Lung Cancer Reveals Prognostic Biomarkers Through Omics Data Integration

Abstract: Non-small cell lung cancer (NSCLC) is one of the most common malignancies worldwide. The development of high-throughput single-cell RNA-sequencing (RNA-seq) technology and the advent of multi-omics have provided a solid basis for a systematic understanding of the heterogeneity in cancers. Although numerous studies have revealed the molecular features of NSCLC, it is important to identify and validate the molecular biomarkers related to specific NSCLC phenotypes at single-cell resolution. In this study, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
(78 reference statements)
1
7
0
Order By: Relevance
“…To characterize the dynamic changes of metabolism in the development of COAD, GSVA was used to calculate the activity of 85 metabolic pathways collected from the MsigDB database in four clinical stages. We found that tumor tissue have activated energy supply compared with normal tissues (Figure 2A), which was consistent with previous studies showing that the activated metabolic microenvironment could supply tumor proliferation and metastasis (Wang et al, 2021). In different stages of tumor development, there are obvious differences in the activity of metabolic pathways.…”
Section: Stage-specific Metabolic and Immune Activitysupporting
confidence: 91%
“…To characterize the dynamic changes of metabolism in the development of COAD, GSVA was used to calculate the activity of 85 metabolic pathways collected from the MsigDB database in four clinical stages. We found that tumor tissue have activated energy supply compared with normal tissues (Figure 2A), which was consistent with previous studies showing that the activated metabolic microenvironment could supply tumor proliferation and metastasis (Wang et al, 2021). In different stages of tumor development, there are obvious differences in the activity of metabolic pathways.…”
Section: Stage-specific Metabolic and Immune Activitysupporting
confidence: 91%
“…Nevertheless, there are still some factors we did not involve, including CEA level, SUVmax, and so on, for the lack of data (not all early-stage lung cancer patients need to take PET-CT and CEA examination). Current data showed that the combined application of multiomics, including liquid biopsy, proteomics, and metabolomics, has widened in predicting the malignancy of small pulmonary nodules (29). We believe that a prospective cohort will be established in the future to develop a more complete model to predict the incidence of lymph node metastasis of early-stage lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 96%
“…To validate the regulatory network changes during lung adenocarcinoma development another set of single cell transcriptome data (GSE123902 [ 27 ], GSE117570 [ 28 ], GSE148071 [ 29 ]) was used as a validation dataset. After quality control, a total of 34,920 cells were selected for subsequent analysis (including 15,701, 14,984, and 4235 cells from distant normal regions of lung samples, early LUAD, and advanced LUAD).…”
Section: Methodsmentioning
confidence: 99%